Several factors that predict the outcome of large B-cell lymphoma patients who relapse/progress after chimeric antigen receptor (CAR) T-cell therapy can be identified before cell administration - Sýkorová, Alice; Folber, František; Polgárová, Kamila; Móciková, Heidi; Ďuraš, Juraj; Steinerová, Kateřina; Obr, Aleš; Heindorfer, Adriana; Ladická, Miriam; Lukáčová, Ľubica; Čellárová, Erika; Plameňová, Ivana; et al. (Cancer medicine, 2024)
AIM: The aim of this study was to analyse the outcomes of patients with large B-cell lymphoma (LBCL) treated with chimeric antigen receptor T-cell therapy (CAR-Tx), with a focus on outcomes after CAR T-cell failure, and to define the risk factors for rapid progression and further treatment. METHODS: We analysed 107 patients with LBCL from the Czech Republic and Slovakia who were treated in ≥3rd-line with tisagenlecleucel or axicabtagene ciloleucel between 2019 and 2022. RESULTS: The overall response rate (ORR) was 60%, with a 50% complete response (CR) rate. The median progression-free survival (PFS) and overall survival (OS) were 4.3 and 26.4 months, respectively. Sixty-three patients (59%) were refractory or relapsed after CAR-Tx. Of these patients, 39 received radiotherapy or systemic therapy, with an ORR of 22% (CR 8%). The median follow-up of surviving patients in whom treatment failed was 10.6 months. Several factors predicting further treatment administration and outcomes were present even before CAR-Tx. Risk factors for not receiving further therapy after CAR-Tx failure were high lactate dehydrogenase (LDH) levels before apheresis, extranodal involvement (EN), high ferritin levels before lymphodepletion (LD) and ECOG PS >1 at R/P. The median OS-2 (from R/P after CAR-Tx) was 6.7 months (6-month 57.9%) for treated patients and 0.4 months (6-month 4.2%) for untreated patients (p < 0.001). The median PFS-2 (from R/P after CAR-Tx) was 3.2 months (6-month 28.5%) for treated patients. The risk factors for a shorter PFS-2 (n = 39) included: CRP > limit of the normal range (LNR) before LD, albumin < LNR and ECOG PS > 1 at R/P. All these factors, together with LDH > LNR before LD and EN involvement at R/P, predicted OS-2 for treated patients. CONCLUSION: Our findings allow better stratification of CAR-Tx candidates and stress the need for a proactive approach (earlier restaging, intervention after partial remission achievement).
Keywords: Humans; receptory antigenů T-buněk; lidé středního věku; Disease Progression; Female; rizikové faktory; mladý dospělý; dospělí; Aged; Receptors, Chimeric Antigen; výsledek terapie; senioři; lidé; Antigens, CD19; doba přežití bez progrese choroby; Slovakia; Slovenská republika; Immunotherapy, Adoptive; Adult; Receptors, Antigen, T-Cell; ženské pohlaví; Male; Middle Aged; difúzní velkobuněčný B-lymfom; antigeny CD19; Treatment Outcome; Czech Republic; Aged, 80 and over; Lymphoma, Large B-Cell, Diffuse; Young Adult; senioři nad 80 let; biologické přípravky; progrese nemoci; chimerické antigenní receptory; Progression-Free Survival; lokální recidiva nádoru; imunoterapie adoptivní; mužské pohlaví; Česká republika; Neoplasm Recurrence, Local; Biological Products; Risk Factors